Monograph of eight simple-club shape clavarioid fungi from Nam Nao national park based on morphological and molecular biological data - Maneevun, Ammanee; Sanoamuang, Niwat (Asia-Pacific Journal of Science and Technology, 2017)
Eight taxa from 2 genera of simple-club shape clavaroid fungi from Nam Nao National Park, Thailand collected during rainy season in 2008-2009 were investigated and illustrated. Identification to species level was based on morphological and molecular characteristics. Monographs of macroscopic fruiting bodies, light and scanning electron microscopic detail of spores, basidia and hyphae were illustrated. A phylogenetic tree was created by analysis of DNA fingerprint using Amplified Ribosomal DNA Restriction Analysis technique (ARDRA) on ITS1-5.8S-ITS2 rRNA gene. All found species were Clavaria falcata Persoon, Clavaria rosea Dalman, Clavaria vermicularis Swartz, Clavaria aurantiocinnabarina Schweinitz, Clavaria miyabeana S. Ito in S. Imai., Ramariopsis fusiformis (Sowerby) R.H. Petersen, Ramariopsis helvola (Pers. Ex. Fr.) R.H. Petersen and Ramariopsis laeticolor (Berkeley & M.A. Curtis) R.H. Petersen. The ARDRA technique was properly used to classify the simple-club shape clavaroid fungi into specific levels. Two species of these, C. falcata Persoon and R. laeticolor (Berkeley & M.A. Curtis) R.H. Petersen are new records for Thailand.